Development of a Silicon Photomultiplier Based Gamma Camera - Tao, Ashley T. (My University, 2012)
Dual modality imaging systems such as SPECT/CT have become commonplace in medical imaging as it aids in diagnosing diseases by combining anatomical images with functional images. We are interested in developing a dual modality imaging system combining SPECT and MR imaging because MR does not require any ionizing radiation to image anatomical structures and it is known to have superior soft tissue contrast to CT. However, one of the fundamental challenges in developing a SPECT/MR system is that traditional gamma cameras with photomultiplier tubes are not compatible within magnetic fields. New development in solid state detectors has led to the silicon photomultiplier (SiPM), which is insensitive to magnetic fields.
We have developed a small area gamma camera with a tileable 4x4 array of SiPM pixels coupled with a CsI(Tl) scintillation crystal. A number of simulated gamma camera geometries were performed using both pixelated and monolithic scintillation crystals. Several event positioning algorithms were also investigated as an alternative to conventional Anger logic positioning. Simulations have shown that we can adequately resolve intrinsic spatial resolution down to 1mm, even in the presence of noise. Based on the results of these simulations, we have built a prototype SiPM system comprised of 16 detection channels coupled to discrete crystals. A charge sensitive preamplifier, pulse height detection circuit and a digital acquisition system make up our pulse processing components in our gamma camera system. With this system, we can adequately distinguish each crystal element in the array and have obtained an energy resolution of 30±1 (FWHM) with Tc-99m (140keV). In the presence of a magnetic field, we have seen no spatial distortion of the resultant image and have obtained an energy resolution of 31±3.
Keywords: silicon photomultipliers; semiconductor detectors; SPECT/MR; dual-modality imaging; Biomedical devices and instrumentation; Biomedical devices and instrumentation